Government intervention, sectoral productivity growth and structural transformation. Issue 16 (20th September 2017) - Liang, Jun; Long, Shaobo
ABSTRACT: This article examines the long-term impact of government intervention and sectoral productivity on structural transformation. We construct a multi-sector Dynamic General Equilibrium model that explicitly incorporates government intervention as a force of structural transformation. The government affects the economy through taxation and lump sum transfers. We show that in the steady state, a reduction in the tax rate and an increase in sectoral productivity will decrease the agricultural employment share, and when nonhomotheticity of preference is strong enough, these changes can also increase the share of services employment.